Maternal and fetal outcome among pregnant women presenting with thrombocytopenia - Chauhan, Vikrant; Gupta, Amit; Mahajan, Neelam; Vij, Anju; Kumar, Rajinder; Chadda, Abhinav (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Thrombocytopenia complicates about 7-8% of all pregnancies. It is an under-explored condition in Indian women during pregnancy, so the study was planned to find out the prevalence and causative factors of thrombocytopenia during pregnancy and to review management strategies for the best feto-maternal outcome. Methods: This prospective study was conducted in the department of obstetrics and gynecology at Dr. Rajendra Prasad Government Medical College Kangra at Tanda, Himachal Pradesh. 546 antenatal women were screened, 65 women who were diagnosed with thrombocytopenia, were included in the study. Results: The incidence of maternal thrombocytopenia in our study was 8.4%. 63% of the women had mild thrombocytopenia while 35.4% and 1.5% of women were moderate and severe thrombocytopenic respectively. The mean maternal platelet count was 106907±30136.52/µL whereas the mean neonatal platelet count was 175307.7±33834.87/µL. The incidence of fetal thrombocytopenia was 3.1%. Amongst 65 thrombocytopenic women 1.5% had HELLP Syndrome, 26.3% had PIH and 68.2% had gestational thrombocytopenia. 27.7% were delivered by LSCS and 72.3% were delivered vaginally. The most common indication of LSCS was acute fetal distress with MSL (55%) followed by breech (25%), failed induction (10%), and the rest (10%) for other obstetrical indications. 30% women required induction of labor with misoprostol for various obstetrical indications. The most common indication for induction was mild pre-eclampsia (45%) followed by IUGR (25%), PROM (15%) and post-date (15%). The mean baby weight in our study was 2.84±0.32 kg. Out of 65 neonates, 6.15% neonates required NICU admission. One neonate died at first post - op day because of respiratory distress syndrome. APGAR score <7 in 1 and 5 min were seen in 6.15% of neonates. Only 8% neonates were small for gestational age. Conclusions: In pregnancy with thrombocytopenia, gestational thrombocytopenia is the commonest and benign condition which does not alter the obstetrical management. Still a vigil should be kept on maternal platelet count in antenatal period to prevent unfavorable outcome in serious conditions that may require specific and urgent management (HELLP syndrome, severe pre-eclampsia, TTP, HUS and acute fatty liver of pregnancy).